Anesthetic Management of Emergency Esophagoscopy for Denture Foreign Body Extraction in an Adult with Uncorrected Pulmonary Atresia–Ventricular Septal Defect, Major Aortopulmonary Collateral Arteries, and Bacterial Pneumonia: A Case Report - Eko Setijanto; Bara Adithya; Adhitya Sakti Nugraha (Journal of Anesthesiology and Clinical Research, 2026)
Introduction: Esophageal foreign body impaction is a common emergency, but its management becomes uniquely complex when superimposed on uncorrected cyanotic congenital heart disease and acute pulmonary infection. Adults with pulmonary atresia–ventricular septal defect (PA-VSD), major aortopulmonary collateral arteries (MAPCA) and patent ductus arteriosus represent a fragile physiology in which any deterioration in cardiac output, oxygenation or systemic vascular resistance may precipitate refractory hypoxemia. Case presentation: A 51-year-old man presented with sudden throat pain after accidentally swallowing a denture. Cervical radiography revealed an irregular opacity at C4–C5. He had longstanding uncorrected PA-VSD with MAPCA, patent ductus arteriosus and moderate aortic regurgitation; echocardiography showed cardiac output 2.9 L/min and cardiac index 1.86 L/min/m². He was concurrently diagnosed with Klebsiella pneumoniae bacterial pneumonia (chest radiograph: cardiothoracic ratio 75% with pulmonary edema; SpO₂ 94% on room air). Following multidisciplinary preoperative optimization—nebulized ipratropium-salbutamol, furosemide, digoxin, lansoprazole, warfarin, bisoprolol and spironolactone—he underwent emergency rigid esophagoscopy under general anesthesia with endotracheal intubation. Hemodynamic-protective induction preserved systemic vascular resistance and avoided hypoxic-hypercapnic shifts. The denture was extracted intact and the patient was transferred to the intensive care unit with blood products on standby. Conclusion: Successful management required prompt diagnosis, multidisciplinary preoperative optimization and a hemodynamic-protective anesthetic plan tailored to balanced systemic-pulmonary circulation. Awareness of the specific physiology of unrepaired PA-VSD with MAPCA and concurrent pneumonia is essential to safe perioperative care.